Towards a collaborative web-based learning system - Tahir, Asni; Tanalol, Siti Hasnah (2004)
The Internet can play an important role in providing education and new opportunities.The availability of the web-enabling technologies has influenced the success of e-learning strategies. The Internet may make the larger world more tangible and give strong foundation to extend traditional learning methods with dynamic learning using web technologies or electronically.E-learning consists of Web-based teaching tools that allow students and instructors access to course materials, assessment tools, activities and various communication options electronically.E-learning continues to work its way into the curriculum of many institutions of higher learning across the country.Focus of this paper is the discussion of the e-learning implementation, including future development and enhancement of e-learning.A review of the literature concerned the role of ICT in enhancing and promoting learning in or using the World Wide Web (WWW or Web) is also included.The e-learning platform used does provide a paradigm shift in facilitating student-lecturer interaction